Handbook for the chemical analysis of plastic and polymer additives. - Bolgar, Michael (Environetbase., 2016)
Most plastics and polymers used for consumer goods and technical applications contain numerous additives, many of which are potentially hazardous to human health and the environment. The Handbook for the Chemical Analysis of Plastic and Polymer Additives provides a detailed reference for the analysis of additives that are most widely used in plastics and polymers. The handbook offers a unique combination of comprehensive chromatograms, mass spectral data, and analytical data in addition to environmental perspectives and regulations issued by the FDA, USEPA, EU agencies, and other gr.